Empowering students through peer assessment: interrogating complexities and challenges. Issue 3 (4th May 2018) - Hogg, Linda Mary
Abstract: This paper describes a self-study of the author's implementation of peer assessment (PA) in an undergraduate education course. The goal was to improve alignment of assessment practice and theory of practice, by introducing PA to empower students and draw on their funds of knowledge. The PA design is described, and student perception data are analysed alongside lecturer reflections. The focus is on elaboration of personal learning points for the author. Findings suggest the success of PA related to students' ideas about its value, highlighting the importance of motivation to engage as peer assessors. Other findings revealed the author's blindspots, because there were ways that her values and beliefs constrained goal attainment, and illuminated next steps.